Sustainable Development Goals and Businesses as Active Change Agents - Chitra S de Silva Lokuwaduge; Ciorstan Smark; Monir Mir (Australasian Accounting, Business and Finance Journal, 2020)
Nations worldwide are expected to be accountable for a sustainable economic development without compromising environmental and social safeguards. Embracing and spreading leadership actions and interactions in relation to sustainability positively contributes to more ethical and responsible leadership which makes business seen as active change agents in enhancing corporate social responsibility and corporate citizenship. Sustainable Development Goals has identified as a common indicator to measure sustainability. Using the role of business as the active change agent, this article highlight how different sectors and business contribute of achieving these goals giving special reference to the Australasian region.
Keywords: Sustainability; Ethics; Business; ESG